If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -3(x + -2) = (7 + -1x) * 4 + -4x Reorder the terms: 7 + -3(-2 + x) = (7 + -1x) * 4 + -4x 7 + (-2 * -3 + x * -3) = (7 + -1x) * 4 + -4x 7 + (6 + -3x) = (7 + -1x) * 4 + -4x Combine like terms: 7 + 6 = 13 13 + -3x = (7 + -1x) * 4 + -4x Reorder the terms for easier multiplication: 13 + -3x = 4(7 + -1x) + -4x 13 + -3x = (7 * 4 + -1x * 4) + -4x 13 + -3x = (28 + -4x) + -4x Combine like terms: -4x + -4x = -8x 13 + -3x = 28 + -8x Solving 13 + -3x = 28 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 13 + -3x + 8x = 28 + -8x + 8x Combine like terms: -3x + 8x = 5x 13 + 5x = 28 + -8x + 8x Combine like terms: -8x + 8x = 0 13 + 5x = 28 + 0 13 + 5x = 28 Add '-13' to each side of the equation. 13 + -13 + 5x = 28 + -13 Combine like terms: 13 + -13 = 0 0 + 5x = 28 + -13 5x = 28 + -13 Combine like terms: 28 + -13 = 15 5x = 15 Divide each side by '5'. x = 3 Simplifying x = 3
| 7x-2x(5y-1)= | | 2-x^2+x=0 | | 15+17=13+14 | | -5(x-3)-7x=-36 | | 4x+3=21-2x | | x*x-3-6x=0 | | -2(1+8)=x | | 4x-4=80 | | 6(x-4)=-2(x+8) | | 10x*8y=960 | | 10+8a=11a-6 | | (x^2+x-4)=0 | | 8x+4y=40 | | 1/2(18x-8)=6x-7/3 | | 6(3-x)-5(2x-4)=4(3x-1)+14 | | 10m=96 | | 2m+5=20-3m | | 7x-5=61 | | 15x+40=175 | | 7x-3=15+x | | 1200=s^2+6s | | x^2+5x-22=0 | | x+72=138 | | 16cos^4x=0 | | 9p-1=2 | | (7x-2)(11x-34)= | | 3r(2r+7)-(r-4)= | | 139-3X=5X+9 | | 4X^2+4X+2=0 | | 5p+28=12p | | 3x+2(7x-13)=-162 | | 240=-7x-3(4x-23) |